Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles. Issue 9 (18th January 2023) - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans‐Georg
Abstract: Current flowing through an electrolyte is accompanied by continuum motion of ions and solvent, species concentration profiles, and the electric field. While,  historically, the understanding of electrolyte transport has predominantly relied on interpreting macroscopic voltage (or current) measurements, recent advances in imaging and spectroscopic techniques allow velocity and concentration profiles to be probed directly. Such detailed information creates exciting opportunities—ranging from verifying theories describing transport in previously studied Li‐ion electrolytes, to new approaches for measuring properties as well as accurately and precisely quantifying transport in more complex electrolytes. Such emerging directions are herein discussed. Abstract : With recent advances in imaging techniques, researchers can visualize the transient behavior of electrolyte species. This perspective describes how such measurements in a polarized electrolyte contain information about species transport and how they connect to the corresponding physics‐based theoretical understanding. Such an approach opens up new possibilities for characterizing and quantifying transport behavior in presently investigated and yet‐to‐be‐discovered electrolytes.